FIVE YEAR FOLLOW-UP OF IMMEDIATE RESTORATION WITH BREDENT IMPLANTS - Mihaela Mitrea; Razvan Tudor Tepordei; Irina Luciana Gurzu; Edlibi Al Hage Walid; Irina Jemnoschi-Hreniuc; Angela Tecuceanu; Allia Dmour; Razvan Radu Maxim; Dumachita-Sargu Bogdan; Mihaela Moscu; Vasile-Deniss Mereuta; Laurian Lucian Francu; et al. (Romanian Society of Oral Rehabilitation, 2023)
The aim of this retrospective study was to evaluate the treatment outcome of All-on-6 and All-on-4 Fast @Fixed from Bredent implants (Brdent GmbH, Senden,Germany) immediately loaded with fixed full-arch prosthesis. Delivering a full arch implant restoration, which transits a patient from the frustartions of edentulism to the stability and function of a fixed prosthesis, is one of the most rewarding experience in dentistry. With the advancement in digital technology and with modified implant design and advance prosthetic options, what started as a two stage delayed loading procedure in the seventies, evolved to immediate implant palcement in extraction sockets and even immediate loading of these implants in a browing number of indications. Within the limits of this small group (n=11 patients/114 implants), the failure rate of the analyzed implant system (n=3 respectiv 2,63% implant loss) seems to be comparable with other immediate-loading protocols. Following this study, we can conclude that the body of the bridge in point contact with the alveolar ridge allows a better sanitation of the prostehtic bridge and thus avoids the occurrence of peri-implantitis. In the case of the bridge bodies that completely cover the vestibular and oral alveolar ridge, we observed an accentuated resorption of the alveolar ridge over time.